Dinamika Komunitas Panahan Muslim di Kalimantan Selatan - Maimanah; Noor'ainah (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2024)
In the last decade, archery has emerged as a distinct trend within the Muslim community of South Kalimantan. It has transcended its status as merely a sport to become a hobby that intertwines with religious discourse, particularly through the narrative of 'nyunnah'. This research aims to explore the dynamics of the archery community among Muslims in South Kalimantan amidst this 'nyunnah' narrative. Utilising a phenomenological approach, data collection was conducted through three primary methods in-depth interviews with members of the Muslim archery community, participatory observation in the field by engaging in various archery activities, and documentation of religious symbols employed, patterns of interaction among members, and the community's adaptation to various challenges. The findings indicate that the Muslim archery community in South Kalimantan is predominantly composed of urban middle-class Muslims, who serve as the principal actors in promoting archery. For this group, archery represents a manifestation and adaptation of religious values. The activity of archery has subsequently evolved to form both personal and collective identities that reflect a contemporary Muslim lifestyle. This phenomenon of archery provides significant insights within the context of contemporary Islamic studies, particularly in understanding the relationship between religion and popular culture.